The Oxford dictionary of world religions - Bowker, John Westerdale (Oxford University Press, 1997)
"The Oxford Dictionary of World Religion is the most wide-ranging A-Z reference guide to all aspects of the world's religions past and present. Whether the reader seeks quick, accessible answers from the short entries or more detailed discussion from the longer more discursive articles, it offers a wealth of unrivalled and unbiased authoritative detail. With a total of over 8,200 entries, an extensive topic index, and an original and in-depth introductory essay this new dictionary, drawing on the latest research, is the definitive compendium on the subject." "Religions; movements, sects, and cults; texts books; individuals; sacred sites; customs; themes on general topics relevant to all religions such as prayer, biogenetics, asceticism, confession, cosmology, art and architecture, music and dance; accessible reference hundreds of quotations many translated specially for this book; and a topic index listing 13,000 entries on major themes such as Brahman, breathing, death beliefs and rituals, heavens and paradises, kami, mandala, mantra, mysticism, Sufism, yoga, and Zen practice."--Book jacket.